Single Nucleotide Polymorphisms (SNPs) Reveal Sibship Among Founders of a Bangladeshi Rohu (Labeo rohita) Breeding Population - Hamilton, Matthew Gray; Mekkawy, Wagdy; Kilian, Andrzej; Benzie, John A. H. (Frontiers in Genetics, 2019)
Rohu (Labeo rohita) is a significant freshwater aquaculture species with approximately 1.8 Mt produced annually. Fin clips obtained from the founders of a newly established Bangladesh-based breeding population (~140 fish from each of the Halda, Jamuna and Padma rivers) were used to identify 9157 SNPs and 14 411 silicoDArT markers using the Diversity Arrays Technology (DArT) genotyping-by-sequencing platform known as using the DArTseqTM platform. After quality control, 1985 SNPs were retained and used to examine population structure within and among river systems. Examination of genomic relationships revealed evidence of full- and half-sibling relationships among founders. Accordingly, sibship and dummy parents were assigned within each river population using a maximum likelihood approach with COLONY software. Founders that had no dummy parents in common were then identified for population genetic analyses. Only 40 unique dummy parents and 17 founders with no common dummy parents were identified from the Halda river, compared with 206 (96) from the Jamuna and 184 (83) from the Padma. Overall pairwise FST estimates among rivers were low (< 0.005) and the optimum number of clusters using unsupervised K-means clustering was one, indicating little genetic divergence among the river populations in our SNPs. These results suggest that observed sibship among founders should be accounted for in future pedigree-based analyses and it cannot be assumed that fertilised spawn collections are representative samples of river populations.